Understanding adherence to self-isolation in the first phase of the COVID-19 pandemic in England: a cross-sectional mixed-methods study - Charlotte Robin; Rosy Reynolds; Helen Lambert; Matthew Hickman; G. James Rubin; Louise E. Smith; Lucy Yardley; Shenghan Cai; Tingting Zhang; Piers Mook; Oliver McManus; Gemma Lasseter; et al. (BMC, 2023)
Abstract Background During the early "containment" phase of the COVID-19 response in England (January-March 2020), contact tracing was managed by Public Health England (PHE). Adherence to self-isolation during this phase and how people were making those decisions has not previously been determined. The aim of this study was to gain a better understanding of decisions around adherence to self-isolation during the first phase of the COVID-19 response in England. Methods A mixed-methods cross sectional study was conducted, including an online survey and qualitative interviews. The overall pattern of adherence was described as never leaving home, leaving home for lower-contact reasons and leaving home for higher-contact reasons. Fisher's exact test was used to test associations between adherence and potentially predictive binary factors. Factors showing evidence of association overall were then considered in relation to the three aspects of adherence individually. Qualitative data were analysed using inductive thematic analysis. Results Of 250 respondents who were advised to self-isolate, 63% reported not leaving home at all during their isolation period, 20% reported leaving only for lower-contact activities (dog walking or exercise) and 16% reported leaving for higher-contact, and therefore higher-risk, reasons. Factors associated with adherence to never going out included: the belief that following isolation advice would save lives, experiencing COVID-19 symptoms, being advised to stay in their room, having help from outside and having regular contact by text message from PHE. Factors associated with non-adherence included being angry about the advice to isolate, being unable to get groceries delivered and concerns about losing touch with friends and family. Interviews highlighted that a sense of duty motivated people to adhere to isolation guidance and where people did leave their homes, these decisions were based on rational calculations of the risk of transmission - people would only leave their homes when they thought they were unlikely to come into contact with others. Conclusions Understanding adherence to isolation and associated reasoning during the early stages of the pandemic is essential to pandemic preparedness for future emerging infectious disease outbreaks. Individuals make complex decisions around adherence by calibrating transmission risks, therefore treating adherence as binary should be avoided.